A new species of catfish, Pterocryptis vorax (Actinopterygii: Siluridae), from northern Borneo - Ng, Heok Hee; Kahar, Rafhiah; Tan, Heok Hui (Zootaxa, 2025)
This study describes Pterocryptis vorax, a new species of silurid catfish from the upper reaches of the Temburong River drainage in Brunei Darussalam, northern Borneo. Pterocryptis vorax is distinguished from congeners in having a unique combination of the following characters: rictal lobe ending at vertical posterior to posterior orbital margin, deep lower jaw with a more gently curved anteroventral margin, a color pattern of densely distributed dark brown patches on the flanks that coalesce to form a reticulate pattern, a dark vertical band at the caudal-fin base, 46–57 anal-fin rays and 48–49 vertebrae. Sexual dichromatism in Pterocryptis is also reported for the first time here.